2000
DOI: 10.1556/004.48.2000.4.9
|View full text |Cite
|
Sign up to set email alerts
|

New Pig Disease in Hungary: Postweaning Multisystemic Wasting Syndrome Caused by Circovirus (Short Communication)

Abstract: Postweaning multisystemic wasting syndrome (PMWS), a new disease in Hungary, was recognized in a swine herd located in Southeast Hungary, during the early winter of 1999. The first clinical signs of paleness, anaemia, and leanness appeared immediately after weaning, at the age of 40-50 days. Pustules were frequently observed on the skin of the trunk, and signs of necrotic dermatitis were also visible. A syndrome of poor growth and wasting was characteristic of the affected pigs. A porcine circovirus (PCV), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The division between 'early' and 'late stage of disease' is rather artificial, but it allowed us to discriminate those pigs that died of PMWS after a very short period of weakness in still good body condition, as described before (Dán et al, 2003), from PMWS cases of a longer clinical evolution that resulted in a clinical condition of wasting. Morbidity and mortality rates on all the eight farms monitored in this study were relatively similar to those observed in other countries where PMWS has been diagnosed (Madec et al, 2000;Kiss et al, 2000;Schmoll et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The division between 'early' and 'late stage of disease' is rather artificial, but it allowed us to discriminate those pigs that died of PMWS after a very short period of weakness in still good body condition, as described before (Dán et al, 2003), from PMWS cases of a longer clinical evolution that resulted in a clinical condition of wasting. Morbidity and mortality rates on all the eight farms monitored in this study were relatively similar to those observed in other countries where PMWS has been diagnosed (Madec et al, 2000;Kiss et al, 2000;Schmoll et al, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…In Europe, PMWS was first reported from France (LeCann et al, 1997) and Spain (Segalés et al, 1997). In addition, the syndrome has also been recognised in countries neighbouring Croatia, such as Slovenia (Toplak et al, 2002), Hungary (Kiss et al, 2000), Austria (Schmoll et al, 2002) and Italy (Martelli et al, 2000).…”
mentioning
confidence: 99%
“…The nucleotide sequence of a PCV-2 virus strain detected from a case of postweaning multisystemic wasting syndrome (PMWS) occurring in a Southern Hungarian pig herd (Kiss et al, 2000) was compared with that of the virus strain found by us. In the 451 base pair long nucleotide sequences nucleotide difference occurred in three places, two of which involved amino acid change.…”
Section: Discussionmentioning
confidence: 99%
“…PCV2 infection associated with PMWS was first detected in Hungary in 1999 (Kiss et al, 2000). The infection was later found to be associated with PDNS (Molnár et al, 2002) as well as PRDC (Szeredi et al, 2013).…”
mentioning
confidence: 99%